First optical observations of interhemispheric electron reflections within pulsating aurora. Issue 6 (22nd March 2017) - Samara, M.; Michell, R. G.; Khazanov, G. V.
Abstract: A case study of a pulsating auroral event imaged optically at high time resolution presents direct observational evidence in agreement with the interhemispheric electron bouncing predicted by the SuperThermal Electron Transport model. "Pulsation‐on" times are identified and subsequent equally spaced fainter pulsations are also noted and can be explained by a portion/percentage of the primary precipitating electrons reflecting upward from the ionosphere, traveling to the opposite hemisphere and reflecting upward again. The high time resolution of these data, combined with the short duration of the pulsation‐on time (∼1 s) and the relatively long spacing between pulsations (∼6 to 9 s) made it possible to observe the faint optical pulses caused by the reflected electrons coming from the opposite hemisphere. Plain Language Summary: This is the first time we show evidence that a certain type of aurora is caused by electrons bouncing back and forth between the two hemispheres. This means that these electrons are responsible for some of the total light in the aurora, a possibility that has largely been ignored in theoretical models. Key Points: First observational verification of reflected electron populations in diffuse aurora The spacing and relative intensity of the observed peaks is consistent with electrons from the opposite hemisphere The observation criteria were met only due to the performing of high time resolution imaging of the diffuse aurora